Comprehensive analysis of IDLC Securities Limited (IDLC SL) during COVID-19 - Auroni, Tasnova Islam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.